New "Hungarian complex" from the excavationsof the Rozhdestvenskoye burial ground - Krylasova, N.B.; Belavin, A.M.; Podosenova, Yu.A. (Perm Federal Research Centre Journal, 2018)
In 2017 a symbolic burial ground (a cenotaph) was found for the first time in Perm region at the Rozhdestvenskoye burial ground. The cenotaph contained a set of precious possessions of a status character: the only saber with a silver pommel on the hilt, a battle axe and other armaments, a silver trapezoidal suspension, a fire striker with a bronze handle, a rich belt set, a funerary mask and other things. The burial ground is a cenotaph, as indicated by the fact that the most valuable things, including the funerary mask, were wrapped in a bundle, tied with a waist belt that was located in the centre of a usual grave pit. All the items of the funeral equipment were deliberately broken, in what appears to be the ritual of "killing" things typical of the Finno-Ugric peoples. The silver objects presented in the complex are stylistically similar to the Hungarian ones, but as far as the technological characteristics are concerned, they gravitate towards the Prikamye jewelry school. They might have been made according to the Hungarian models. The military complex of the "Hungarian type", typical of rich druzhina (fellowship) burial grounds of the Perm Cis-Urals, evidently belonged to a man-soldier who died elsewhere, a representative of the social elite.